THE IMPACT OF NATURAL AND CLIMATIC CONDITIONS ON THE DEVELOPMENT OF ANCIENT KHOREZM CULTURES OF THE BRONZE AGE - Ismailov, Ulugbek (Oriental Journal of History, Politics and Law, 2025)
This article examines the impact of ecological factors on the formation of Bronze Age cultures in the Khorezm oasis. The focus is on changes in the natural environment, water resource management, and population adaptation strategies to ecological conditions. The study utilizes recent archaeological discoveries, paleoclimatological data, and historical sources to analyze the influence of environmental processes on cultural evolution in the region.